2021
DOI: 10.1021/acsomega.0c05615
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Methane–Propane Hydrate Formation by the Use of Different Impellers

Abstract: In the present study, the effect of different kinds of impellers with different baffles or no baffle was investigated. Up-pumping pitched blade turbine (PBTU) and Rushton turbine (RT) were the two types of impellers tested. The reactor was equipped with different designs of baffles: full, half and surface baffles, or no baffles. Single (PBTU or RT) and dual (PBTU/PBTU or RT/RT) use of impellers with full (FB), half (HB), surface (SB), and no baffle (NB) combinations formed two sets of 16 experiments. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Both pseudo-first- and pseudo-second-order kinetics models gave a closer value of adsorption ( Figure 7 and Figure 8 ). This shows that the pseudo-first and pseudo-second-order kinetics models both fit for adsorption kinetics [ 43 , 44 , 45 , 46 , 47 ]. However, Q e with a lower experimental value was found in pseudo-second order, and vice versa in pseudo-first order.…”
Section: Resultsmentioning
confidence: 86%
“…Both pseudo-first- and pseudo-second-order kinetics models gave a closer value of adsorption ( Figure 7 and Figure 8 ). This shows that the pseudo-first and pseudo-second-order kinetics models both fit for adsorption kinetics [ 43 , 44 , 45 , 46 , 47 ]. However, Q e with a lower experimental value was found in pseudo-second order, and vice versa in pseudo-first order.…”
Section: Resultsmentioning
confidence: 86%
“…24,25 These include mixing/agitating the sample using stirred reactor, rocking cells, and spraying the water into pressurized reactors using the high-pressure pumps. [26][27][28] Organic solvents and porous materials are also being studied to address these problems. [29][30][31] The search for novel material is still pursued to accelerate these processes for rapid kinetics and higher hydrate conversion.…”
Section: Methane Gasmentioning
confidence: 99%
“…A number of interesting papers due to Longinos and Parlaktuna (Longinos & Parlaktuna [36][37][38][39] ) discuss interesting experiments on hydrate formation dynamics and effects of various types of chemicals that change hydrate formation dynamics. While these are very interesting papers, they stretch outside the main focus of this work.…”
Section: Co 2 /Ch 4 Hydrate Exchange For Combined Safe Co 2 Storage and Energy Productionmentioning
confidence: 99%
“…In the absence of induced hydrodynamics, it has been demonstrated that slow mass transport through blocking hydrate films can predict experimental induction times (Kvamme et al 27 ). Another aspect related to the papers by Longinos and Parlaktuna [36][37][38][39] is the effect of selective adsorption of hydrate that forms on water surfaces, which, for instance, implies that adsorption of propane on liquid water surface will dominate compared with adsorption of methane (Kvamme 7 ). In summary, comparison with theories and experimental papers on hydrodynamic level requires a different theoretical approach than what is discussed here.…”
Section: Co 2 /Ch 4 Hydrate Exchange For Combined Safe Co 2 Storage and Energy Productionmentioning
confidence: 99%
See 1 more Smart Citation